Last Day Every Day: Figural Thinking from Auerbach and Kracauer to Agamben and Brenez - Martin, Adrian (punctum books, 2012)
Where is film analysis at today? What is cinema theory up to, behind our backs? The field, as professionally defined (at least in the Anglo-American academic world), is presently divided between contextual historians who turn to broad formations of modernity, and stylistic connoisseurs who call for a return to old-fashioned things like authorial vision, tone, and mise en scène. But there are other, vital, inventive currents happening - in criticism, on the Internet, in small magazines, and renegade conferences everywhere - which we are not hearing much about in any official way. Last Day Every Day shines a light on one of these exciting new avenues. Is there a way to bring together, in a refreshed manner, textual logic, hermeneutic interpretation, theoretical speculation, and socio-political history? A way to break the deadlock between classical approaches that sought organic coherence in film works, and poststructuralist approaches that exposed the heterogeneity of all texts and scattered the pieces to the four winds? A way to attend to the minute materiality of cinema, while grasping and contesting the histories imbricated in every image and sound?